Impact of viral infections in children with community‐acquired pneumonia: results of a study of 17 respiratory viruses. Issue 1 (13th February 2012) - Esposito, Susanna; Daleno, Cristina; Prunotto, Giulia; Scala, Alessia; Tagliabue, Claudia; Borzani, Irene; Fossali, Emilio; Pelucchi, Claudio; Principi, Nicola
Abstract : Please cite this paper as: Esposito et al. (2012) Impact of viral infections in children with community‐acquired pneumonia: results of a study of 17 respiratory viruses. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2012.00340.x. Background Little is known about the prevalence of viral infections in children with community‐acquired pneumonia (CAP). Objectives To describe the clinical and virological data collected from children with radiographically confirmed CAP in whom 17 respiratory viruses were sought in respiratory secretion samples during the acute phase of the disease. Patients and methods The study involved 592 children with radiographically confirmed CAP whose respiratory secretion samples were tested using the Luminex xTAG Respiratory Virus Panel Fast assay, which simultaneously detects influenza A virus, influenza B virus, respiratory syncytial virus (RSV)‐A and ‐B, parainfluenzavirus‐1, ‐2, ‐3, and ‐4, adenovirus, human metapneumovirus, coronaviruses 229E, NL63, OC43, and HKU1, enterovirus/rhinovirus, and bocavirus. A real‐time PCR assay was used to identify the rhinovirus in the enterovirus/rhinovirus‐positive samples. Results A total of 435 children (73·5%) were positive for at least one virus: the most frequently detected was RSV, which was found in 188 (31·7%), followed by rhinovirus ( n = 144, 24·3%), bocavirus ( n = 60, 10·1%), influenza viruses ( n = 57, 9·6), and hMPV ( n = 49, 8·2%). Viral co‐infections were found in 117 children (19·7% of the enrolled children; 26·9% of those with viral infections). Marginal differences were found between the infections owing to a single virus. Co‐infections showed radiographic evidence of alveolar pneumonia significantly more frequently than single infections (OR 1·72, 95% CI 1·05–2·81). Conclusions The findings of this study highlight the importance of respiratory viruses (mainly RSV and rhinovirus) in children with CAP and show the characteristics of both the single infections and co‐infections associated with the disease.